Critical evaluation of mentoring programmes in theological seminaries of the Evangelical Church of West Africa (ECWA) - Chiroma, Nathan Hussaini (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2012.